2013
DOI: 10.1152/ajpendo.00291.2013
|View full text |Cite
|
Sign up to set email alerts
|

Materno-fetal transfer of docosahexaenoic acid is impaired by gestational diabetes mellitus

Abstract: Better knowledge on the disturbed mechanisms implicated in materno-fetal long-chain polyunsaturated fatty acid (LC-PUFA) transfer in pregnancies with gestational diabetes mellitus (GDM) may have potentially high implications for later on in effective LC-PUFA supplementation. We studied in vivo placental transfer of fatty acids (FA) using stable isotope tracers administrated to 11 control and 9 GDM pregnant women (6 treated with insulin). Subjects received orally [(13)C]palmitic, [(13)C]oleic and [(13)C]linolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 36 publications
3
58
0
Order By: Relevance
“…The initial syncytiotrophoblast concentration was C S (0) = (c mv (0) + c fv (0))/2, as an estimated value according to the overall gradient expected at time 0. In addition, it was assumed that the endogenous pool was large, with C P (0) >> K m (33) and C P (0) >> C S (0). Thus, equations 10 and 11 can be simplified as:…”
Section: Endogenous (Unlabeled) Fatty Acid Modeling Simulationsmentioning
confidence: 99%
“…The initial syncytiotrophoblast concentration was C S (0) = (c mv (0) + c fv (0))/2, as an estimated value according to the overall gradient expected at time 0. In addition, it was assumed that the endogenous pool was large, with C P (0) >> K m (33) and C P (0) >> C S (0). Thus, equations 10 and 11 can be simplified as:…”
Section: Endogenous (Unlabeled) Fatty Acid Modeling Simulationsmentioning
confidence: 99%
“…However, an abnormal placental function, as occurs in GDM or intrauterine growth retardation, could disturb the materno-fetal LC-PUFA transport, with unknown consequences for the neurodevelopment of the offspring. Because placental lipid pools serve as a relay towards transport to the fetus, we studied in humans the in vivo placental transfer of FA using labeled FA with stable isotopes [26] . Eleven controls and 9 pregnant women with GDM received orally 13 C-palmitic, 13 C-oleic, and 13 Clinoleic acids and 13 C-docosahexaenoic acid ( 13 C-DHA) 12 h before an elective caesarean section.…”
Section: Perinatal Risk Factors For Fetal Overgrowthmentioning
confidence: 99%
“…That the maternal hyperlipidemia in GDM is mainly a hypertriglyceridemia has been indicated by the higher concentration of labeled non-LC-PUFA in the maternal plasma triglycerides of GDM patients compared to controls [26] . In type 2 diabetes, it has been reported that insulin resistance causes high postprandial levels of triglyceride-rich lipoproteins and a prolonged presence in the circulation [27] .…”
Section: Perinatal Risk Factors For Fetal Overgrowthmentioning
confidence: 99%
“…Another RCT using a supplementation of 600 mg reported increased maternal but not fetal DHA levels in pregnant patients with GDM [33]. This finding could be explained by an impaired DHA transfer across the placenta due to GDM as reported by Pagan et al using stable isotope tracers for dynamic studies in vivo [34]. A prospective study on maternal fatty acids concentrations during the third trimester also showed that they were lower in patients with GDM.…”
Section: Dha and Gestational Diabetesmentioning
confidence: 86%